(untitled) (The Quintessential, 2025)
Global plastic pollution reported that; 1 million plastic bottles bought every minute, 100,000 marine animals killed by plastic each year, 500 years to degrade in the environment, 90% of bottled water contain plastic particles. Ethiopia is facing rapid urbanization and industrialization leading to packing of different industrial products with plastic bottles which finally becomes waste and on the other side pavements is behaving different structural failure and surface defects before the end of construction period and service year. In order to minimize the above serious problems, this research was initiated to do experimental investigation of waste plastic bottle as partial replacement of aggregate in bituminous concrete mix through dry process to enhance the desired performance of bitumen concrete mix and to reduce plastic bottles disposal problem. Before applying PET bottles as additives, optimum bitumen content was determined for conventional bitumen concrete mix which is selected as 5.33%; up on which the effect of PET bottles was experimented. Waste plastic bottles are collected and cut in to pieces using scissors. Then it was melted in oven at 180⁰c for 30 minute. Then after cooling down it was pulverized. Finally weighing the required amount of pulverized plastic and replacing the aggregate by 0%, 4%, 6%, 8% and 10% by weight of aggregate, the marshal test were held and volumetric properties on each specimen were computed. Based on the laboratory result, the optimum plastic content was selected at the specimens that have high stability; high bulk density and minimum air void values are 20.66 KN, 2.59gm/cm3 and 3.25% respectively. The optimum plastic content is selected at 4% of plastic bottle by weight of aggregate. Lastly this study concluded that, partial replacement of aggregate by waste plastic bottle can increase the overall performance of bitumen concrete mix. Finally this study recommends it is better to apply this new construction technology on the ground and to adopt it. It is better to know the cost benefit analysis on partial replacement of aggregate by waste plastic bottles in flexible pavements. Keyword:- Bitumen Concrete, Modified Bitumen, Optimum Binder Content, Optimum Plastic Content, Plain Bitumen Experimental Investigation of Waste Plastic Bottles as Partial Replacement of Aggregates in Flexible Pavements.